Evaluation of query-expansion facilities of World Wide Web search engines - Teo, Boon Chin. (2011)
There are many non fee-based search engines for the World Wide Web. The recent introduction of query expansion facility in search engines helps to reduce information overload for the user. This study evaluates the query expansion facility of three search engines, AltaVista™, Excite™ and HotOIL™, in terms of the interactive interface, bookmark facility, refinement ability, quantity and quality of expanded terms and retrieval precision using the expanded terms.